Kalsium Hipoklorit (CaClO2) sebagai Pengganti Larvasida Aedes Aegypti - Herdianti, Herdianti; Sari, Novela; Saputra, Roni; Hariansyah, Fitra Dwi (Jurnal Kesehatan, 2020)
Dengue Hemorrhagic Fever (DHF) prevention can be done by eradicating Aedes aegypti larvae. One way to control larvae is by using larvicide biological or chemical. One type of larvicide that can be used is Calcium Hypochlorite (chlorine) as a substitute for S-Methoprene. The research objective was to determine the effectiveness of chlorine against the mortality of Aedes Aegyptus larvae. This study was an experimental study using three repetitions, the chlorine used consisted of doses of 1,0mg/l, 2,0mg/l, 3,0mg/l, 4,0mg/l, and 5,0mg/l which is applied with 1 liter of water that has been filled with 10 pcs of 3rd instar larvae. Data analysis used a completely randomized design by looking at the percentage of larval mortality within 15 minutes. The data on the number of deaths obtained were analyzed using the Anova test. Statistical results show that there is a difference in the number of deaths of Aedes aegypti larvae from each dose. The most effective dose of chlorine is 5,0mg/l. In conclusion, the more chlorine dose, the faster it will kill the larvae of Aedes aegypti larvae.Â